Evaluation of Academic Enhancement Program for Low-Income Students in Rural Malaysia - Ahmad, Siti Rozaini; Samsudin, Mazliyaton; Adenan, Mohd Noor Farzli; Zulkifli, Muhamad Fikhri; Suhaimi, Ahmad Iqbal Hakim (Journal of Technical Education and Training, 2024)
Malaysia National Science, Technology and Innovation policy 2021-2023 highlighted that Science, Technology, Engineering and Mathematics (STEM) Education plays an important role for Technical and Vocational Education and Training (TVET). Many countries are now keen on integrating STEM into TVET education to maintain competitiveness and prepare the workforce to be more effective and productive in the knowledge-based economy. Penang Regional Development Authority (PERDA) initiated the B40@PERDA Academic Enhancement Programme to enhance the academic performance of primary and secondary school students from the B40 group, focusing on critical subjects. The study aims to evaluate the program’s effectiveness and gauge student and teacher satisfaction. Using a quantitative approach, data were collected via questionnaires from students and teachers at various educational institutions. Respondents were randomly selected to ensure accurate representation. Analysis results showed that more than 95% of primary school students achieved the minimum proficiency level in EMAS with a minimum of 10% reaching the highest proficiency. For secondary school students, at least 50% attained at least a C grade in EMAS and 45.77% did so in Elective Science subjects (Physics, Chemistry, Biology, and Additional Mathematics). This study concluded that the B40@PERDA programme significantly improves EMAS proficiency among rural students and helps reduce dropout rates in these subjects. Furthermore, this programme is crucial for fulfilling the minimum requirements for TVET. By enhancing proficiency in critical subjects such as English, Mathematics, and Science, the B40@PERDA Programme ensures that students are better prepared for TVET pathways, ultimately contributing to their future career opportunities and the development of skilled labor in the region.